Avaliação de dois modelos de vermicompostagem para gerenciamento de resíduos orgânicos crus e aplicação como tema de educação ambiental no ensino formal - Vaz, Ana Claudia Nüernberg (2017)
Of the total urban solid waste generated in Brazil, 51% is organic waste disposed in landfills. The National Solid Waste Policy is part of the National Environmental Policy and articulates with the National Environmental Education Policy, and indicates the recognition of reusable and recyclable solid waste as an economic good, of social value, as a promoter of citizenship, a generator of jobs and income. The organic waste generated at the Federal Technology University of Paraná - UTFPR campus Curitiba, served as a case study to evaluate the management and treatment of organic waste using vermicomposting, which requires less space and serves as a promoter of Environmental Education - EE for teaching. For the management of large-scale organic waste, such as UTFPR University Restaurant-UR, the separation of residues in the kitchen was verified, the amount generated during a week of both raw and leftover waste from the buffet and dish. Two models of vermidigestors were used in duplicate, one consisting of boxes with the bottom modified with holes and another with bars. The most commonly generated raw organic residues were leaves of lettuce, cabbage and cucumber peels. Each of these vegetables was chopped separately to compose the food substrate, and to form the initial substrate that goes into the vermidigestores, 10 kg of humus were added with 1.21 kg of earthworms othe species Eisenia fétida per m2. The experiment was conducted in 60 days with only one feeding application. Samples of vermicompost and leachate were collected every three days to analyze the parameters temperature, humidity, pH, amount of leachate, humic substances, Coliforms, Salmonella, C / N ratio, macro and micronutrients. The results presented average temperature of 23ºC; The average humidity of 81%; The pH remained constant at 7.7; Coliforms and Salmonella were found below the established limit, and the mean C / N ratio in vermicompost and manure was 10.8 / 1. The analysis of micro and macro nutrients indicated a fertilizer rich in nitrogen and high amount of iron for both models. It was observed that the model of vermidigestor with bars obtained better result when evaluating the decomposition of the labile organic matter, leachate flow and reproduction of the earthworm population, being this model the one indicated for large scale management. For small scale application the two models are suitable. The box vermicomposting technique was applied in the EE activity from a primary school, identifying the difficulties and questions of the teachers, provided subsidies for the development of two booklets, one for the infantile public and another one for the adult public.